The Effect of Religiosity, Halal Knowledge, Subjective Norm on Purchase Intention of Halal Cosmetic Mediated by Attitude Among Millennials in West Sumatera - Khaira Ummah, Kuntum; Verinita Verinita; Maruf Maruf (Dinasti Review, 2025)
This study examines the impact of Religiosity, Halal knowledge, and Subjective norm on Purchase Intention mediated by Attitude among millennials in West Sumatera. This study uses quantitative methods with purposive sampling of 168 respondents who know and are interested in buying halal cosmetics. Data collection was conducted using Google Forms, distributed online, and analyzed using SmartPLS 4.0. This study explores the impact of religiosity, subjective norm, and halal knowledge on attitude and purchase intention. The results reveal that religiosity and subjective norm positively and significantly influence attitude and purchase intention. Meanwhile, halal knowledge positively and significantly affects attitude but does not significantly affect purchase intention. Additionally, attitude has a positive and significant influence on purchase intention. Furthermore, religiosity, halal knowledge, and subjective norm positively and significantly affect purchase intention through the mediating role of attitude. These findings emphasize the crucial role of consumer attitudes in shaping purchase intention, particularly in contexts influenced by religious, knowledge, and subjective norm.